Tinjauan Yuridis Terhadap Putusan Hakim Dalam Kasus Tindak Pidana Pencurian (Studi Kasus Putusan No.01/Pid/2023/PN.Baubau) - LM Al Gafur Rahim; Mashendra; Samsul (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aims to analyze the judge’s legal considerations in Baubau District Court Decision Number 01/Pid/2023/PN Baubau concerning the crime of theft and the application of criminal law to the defendant. The study employs a normative legal research method using statutory and case approaches. Data were obtained through a literature review of legislation, court decisions, and relevant legal literature, and were analyzed descriptively and qualitatively. The findings indicate that the Panel of Judges applied Article 362 of the Indonesian Criminal Code by considering the fulfillment of the elements of theft, namely any person, taking an object, property belonging to another person, and the intent to possess it unlawfully. The judge’s considerations were based on juridical aspects, including valid evidence, and non-juridical aspects, such as aggravating and mitigating circumstances. The decision reflects legal certainty, justice, and utility, while emphasizing proportional sentencing based on the defendant’s fault and the consequences of the offense.